The Effect of Organization Commitment to Performance of Kebangkitan Bangsa Party Members of Indonesian Parliament - Jazilul Fawaid; Yetti Supriyati; R. Madhakomala; Zahera Mega Utama (Journal of Business and Behavioural Entrepreneurship, 2019)
Partai Kebangkitan Bangsa (PKB) a party who carried the spirit of pluralism, democracy and has a long history of fighting for the rights of Indonesian to live safely, peacefully and comfortably. PKB Faction in DPR, 47 people sits in Indonesian Parliament, had a big mandate but the performance is bad. Commitment to an organization is an effective response (attitude) that results from evaluating work situations that connect or attach individuals to the organization. This study aims to determine the relationship between organizational commitments to their performance, especially in the PKB members’. This study uses a quantitative approach, survey methods and regression analysis techniques. In organizational commitment to PKB DPR RI members, they should have what is associated with a sense of identification (trust in organizational values), involvement (willingness to do their best for the sake of the organization) and loyalty (the desire to remain a member of the organization concerned). The results of this study indicate that the relationship between organizational commitment and the performance of members of the PKB faction is significantly correlated, means that board members who have high organizational commitment will have a good The implication is an effort that can be made by the leadership by understanding and uniting the perceptions of FPKB DPR RI members who works in DPR to create a conducive working atmosphere.